SFPE engineering standard on calculation methods to predict the thermal performance of structural and fire resistive assemblies (Society of Fire Protection Engineers, 2015)
Annotation This standard provides requirements for the development and use of methods to predict the thermal response of structures using listed fire resistive assemblies to time dependent thermal boundary conditions imposed by fires.
"SFPE S.02 2015."
Keywords: Fire prevention -- Standards.; Fire protection engineering -- Standards.; Heat -- Transmission.; Heat -- Radiation and absorption.; elektronické knihy; electronic books